Factors Associated with Apgar Score among Newborns Delivered by Cesarean Sections at Gandhi Memorial Hospital, Addis Ababa - Mohammed Suleiman Obsa; Getahun Molla Shanka; Misrak Woldayohannes Menchamo; Robera Olana Fite; Meron Abrar Awol (Hindawi Limited, 2020)
Background. Newborns can be assessed clinically using the Apgar score test to quickly and summarily assess the health of newborn physical condition immediately after delivery and to determine any immediate need for extra medical or emergency care. This study is aimed at assessing factors associated with Apgar score among newborns delivered by cesarean sections and factors associated with Apgar score. Method. Institutional-based cohort study design was conducted. All eligible study participants were included. Training was given for data collectors and supervisors. Regular supervision and follow-up was made. Data was entered into Epi Info version 7 computer software by investigators and was transported to SPSS version 20 computer program for analysis. Bivariate and multivariate analysis was used to identify factors associated with Apgar score. Result. A total 354 newborn babies were included into the study. Majority of baby had low Apgar score at one minute and high Apgar score at five minutes. About 30.2% of newborn baby had Apgar score below seven minutes. On the other hand, about 12.8% of all newborns had low Apgar score at five minutes. It had been found that those neonates who were born when skin incision to delivery time is greater than three minutes were about fourfolds more likely to have low Apgar score than those who were born when skin incision to delivery time is less than three minutes (AOR 3.645) (95% CI (0.116-26.421)). Conclusion. Newborn babies have a low Apgar score at one minute as compared to five minutes. But low Apgar score at five minutes has long-term sequel. Therefore, it is very important to reduce factors associated with low Apgar score at both minutes.